Treatment of oilfield-produced water using biological and membrane processes - Pendashteh, Alireza (2010)
Oil and gas fields’ wastewater or “produced water” is the largest waste stream generated in the extraction and process of crude oil and natural gas. It is characterized by high concentration of total dissolved solids (TDS) and dissolved and dispersed hydrocarbon compounds. Due to the increasing volume of waste all over the world in the current decade, the outcome and effect of discharging produced water on the environment has lately become a significant issue of environmental concern and the interest in reusing produced water is increasing in water-stressed regions. In order to treat and reuse produced water, removing of organic and inorganic constituents may be necessary. The main goal of this research was to investigate the feasibility of using a sequencing batch reactor (SBR) and a membrane sequencing batch reactor (MSBR) to remove the organic matters present in produced water. In order to meet this objective, halophilic hydrocarbon degrading microorganisms were used as seed culture to the SBR. Each of the treatment systems was investigated with different feeds including synthetic and real produced water. In order to find major foulants on the membrane surface, the characterization of fouling cake layer was studied. Different chemicals were used to find the optimum procedure for membrane cleaning. Both the SBR and MSBR systems were capable of removing the hydrocarbons from synthetic and real produced water. For the SBR, at TDS concentration of 35,000 mg/L, hydraulic residence time (HRT) of 20 h and an organic loading rate (OLR) of 1.8 kg chemical oxygen demand (COD)/(m3d), COD and oil and grease (O&G) removal efficiencies for synthetic produced water were more than 90%. However, with increase in salt content to 250,000 mg/L, COD and O&G removal efficiencies decreased to 74% and 63%, respectively. The results of biological treatment of real produced water showed that at the same HRT, the removal rates of main pollutants of wastewater such as COD, total organic carbon (TOC) and O&G were above 81, 83, and 85%, respectively. For the MSBR, at an OLR of 1.124 kg COD/(m3d), an HRT of 20 h and TDS of 35,000 mg/L, removal efficiencies of 97.5, 97.2 and 98.9% of COD, TOC and O&G, respectively were achieved. Treating of the real produced water showed removal rates of 86.2, 90.8 and 90.0% for the same conditions. However with increasing salt content, the COD removal efficiencies of the synthetic and real produced water were reduced to 90.4 and 17.7%, respectively at the highest TDS. The MSBR receiving synthetic hypersaline oily wastewater was modeled by artificial neural network (ANN). A feed-forward neural network trained by batch back propagation algorithm was employed to model the MSBR. A set of 193 operational data from the wastewater treatment with the MSBR was used to train the network. The training, validating and testing procedures for the effluent COD and TOC concentrations were successful and good correlations were found between the measured and predicted concentrations (R2 of 0.9525 and 0.9563, respectively for the two parameters mentioned). Foulant characterization showed that membrane fouling layer is governed by the deposition of organic and inorganic substances composed of extracellular polymeric substances (EPS), hydrocarbon components and inorganic matters. Membrane cleaning tests showed that one stage cleaning of different cleaning agent can not recover flux effectively; however the two stages NaOCl followed by acid provided effective flux recovery.